CONSUMER ACCEPTANCE STUDYTOWARDFRESHWATER MUSSEL - Purnama Simamora; Desmelati Desmelati; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             This research aims to understand the consumer acceptance rate and chemical aspect towards freshwater mussel (Anadontasp) biscuit. Main ingredient used in freshwater mussel biscuit was fresh freshwater mussel from Sei Paku, Kampar Kiri districts Kampar regency. Method used in this research was expreimental method. Design used was completely  randomized design non factorial with 3 used treatments degree 20 g freshwater mussel (B1), 40 g freshwater mussel (B2), and 60 g freshwater mussel (B3) with 3 times repetitions. The result showed that based on consumer acceptance rate in freshwater mussel biscuit processing with different freshwater mussel meat that formulation with 40 g freshwater mussel meat (B2) was the most favor by general which affected consumer acceptance characteristic with golden yellow appearance, mussel meat flavor more precise, specific mussel aroma, and meat texture savory and solid. Based on quality parameter that freshwater mussel biscuit affected organoleptic value (appearance, flavor, aroma) and did not affect texture value, also affected on proximate water content value (8,39%), protein content (9,56%), fat content (8,44%) and ash content (0,89%). Keywords: biscuit, Anadonta sp, consumer acceptance